Analisis Yang Sakral Sumbu Filosofis Yogyakarta Dalam Pemikiran Mircea Eliade - Haq, Siti Ahsanul (Pascasarjana IAIN Metro, 2023)
Yogyakarta has a landscape created from the installation of Javanese people interpreting their world in the image of a city structure known as the Yogyakarta Philosophical Axis. This Philosophical Axis contains deep philosophical values and a complex spatial structure that describes the journey of human life that is difficult to separate from the life of Yogyakarta society. Its values contain an inseparable sacredness that has become a unity in the Yogyakarta Philosophical Axis. Mircea Eliade developed two concepts called the Sacred and the Profane. The designed urban structure creates remarkable value which was created by through the integration of heritage objects with one connected road. The series of meaningful religious conceptions and cosmological images are transformed by the image of the city of Yogyakarta. This research uses a literature review research method by utilizing the sources that are related to and support this research. Through the complexity and deep philosophical values possessed by the city of Yogyakarta, researchers are interested in knowing how Mircea Eliade's perspective on the Sacred and Profane is on the philosophical axis of Yogyakarta.